Analisis Peran Program Keluarga Harapan Terhadap Akses Kesehatan Dan Pendidikkan Pada Keluarga Penerima Manfaat - Bismi Rahma Putri; Ifdal; Osmet (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
The purpose of this study was to determine the implementation of the family of hope program in Nagari Koto Baru Simalanggang, health access for pregnant women and children under five from KPM (beneficiary families) PKH (family hope program). The number of research samples was 170 KPM from 295 KPM in Nagari Koto Baru Simalanggang. Data analysis was descriptive research method with an interview approach and supported by qualitative data. Quantitative data was collected using a questionnaire. While qualitative data was obtained through observation, observation, in-depth interviews with respondents and informants as outlined in the form of interview notes. The results showed that the Family Hope Program in Koto Baru Simalanggang had been well implemented in accordance with the technical instructions for implementing the program starting from receiving social assistance to the program mentoring process. , group activities and individual commitments as well as mutually reinforcing non-cash support for behavior change and access to education and health